African Honey Bee, Africanized Honey Bee, Killer Bee, Apis mellifera scutellata Lepeletier (Insecta: Hymenoptera: Apidae) - James D. Ellis; Amanda Ellis (EDIS, 2009)
Revised! EENY-429, a 7-page illustrated fact sheet by James D. Ellis and Amanda Ellis, is part of the Featured Creatures collection. It describes a subspecies of western honey bee occurring naturally in sub-Saharan Africa that has been introduced into the Americas — distribution, description, life cycle and biology, public risks, economic impact, and management. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009. Revised November 2009.